Magical Realist Motors and the Fictive Chats of the Dead of the Sri Lankan Civil War in Karunatilaka’s The Seven Moons of Maali Almeida - Shaheen, Aamer; Salman, Muhammad; Qamar, Sadia (Pakistan Languages and Humanities Review, 2023)
This paper closely reads Shehan Karunatilaka’s The Seven Moons of Maali Almedia (2022) as a fictive response to the Sri Lankan Civil War. Using Maggie Ann Bowers’ Magic(al) Realism and Anne C. Hegerfeldt’s Lies that Tell the Truth: Magic Realism Seen Through Contemporary Fiction from Britain, as a base for theoretical framework, the paper explores various elements of the Sri Lankan Civil War and exposes the war brutalities as a major exploitation of the human rights. The paper also focuses on the fictive depictions of the role of the international powers in providing arms to both the Sri Lankan government and the state declared terrorist outfits like LTTE. Exploring nexus of global powers, it explores the sponsorship of the terrorism in the guise of NGOs. Finally delving deep, this paper unfolds the agenda of different factions of the war like JVP and satanic faces of the state ministers who protected themselves by some illogical magic charms while burning their own ethnic minorities.